2021
DOI: 10.1029/2021ja029836
|View full text |Cite
|
Sign up to set email alerts
|

An Unusually Large Electron Temperature Increase Over Arecibo Associated With an Intense Geomagnetic Storm

Abstract: Being one of the most significant disturbances of the Earth's magnetosphere, geomagnetic storms exert a great impact on the space environment of the Earth. Thermospheric and ionospheric responses to geomagnetic storms have been extensively investigated in the past few decades (e.g.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…In recent years, the studies on ionospheric storms have been accuracy and regionalization due to the development of ionospheric detection methods and observation data (e.g., Chen et al, 2016;Deng et al, 2011;Dmitriev et al, 2013;Fejer et al, 2014;Jakowski et al, 1990;Li et al, 2010Li et al, , 2020Lv et al, 2021;Ma et al, 2021;Matamba et al, 2016;Qian et al, 2015;Su & Wang, 2022;Zettergren & Snively, 2019). For example, Gong et al (2013) investigated the response of the F region and the topside ionosphere to a strong geomagnetic storm during August 2011, using observation data from the Arecibo Incoherent Scattering Radar (ISR).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, the studies on ionospheric storms have been accuracy and regionalization due to the development of ionospheric detection methods and observation data (e.g., Chen et al, 2016;Deng et al, 2011;Dmitriev et al, 2013;Fejer et al, 2014;Jakowski et al, 1990;Li et al, 2010Li et al, , 2020Lv et al, 2021;Ma et al, 2021;Matamba et al, 2016;Qian et al, 2015;Su & Wang, 2022;Zettergren & Snively, 2019). For example, Gong et al (2013) investigated the response of the F region and the topside ionosphere to a strong geomagnetic storm during August 2011, using observation data from the Arecibo Incoherent Scattering Radar (ISR).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the studies on ionospheric storms have been accuracy and regionalization due to the development of ionospheric detection methods and observation data (e.g., Chen et al., 2016; Deng et al., 2011; Dmitriev et al., 2013; Fejer et al., 2014; Jakowski et al., 1990; Li et al., 2010, 2020; Lv et al., 2021; Ma et al., 2021; Matamba et al., 2016; Qian et al., 2015; Su & Wang, 2022; Zettergren & Snively, 2019). For example, Gong et al.…”
Section: Introductionmentioning
confidence: 99%
“…Lv et al. (2021) investigated the response of F region electron temperature to the August 2011 storm using the measurements of Arecibo (18.3°N, 66.7°W) incoherent scatter radar and proposed an enhancement of the F‐region electron temperature by 800 K resulting from neutral composition changes.…”
Section: Introductionmentioning
confidence: 99%
“…increases by ∼1,000 K near 350 km and the enhancement becomes smaller in higher altitudes during the August 2011 storm, and suggested that temperature increase is consistent with reduced electron density and electron-ion cooling rate. Lv et al (2021) investigated the response of F region electron temperature to the August 2011 storm using the measurements of Arecibo (18.3°N, 66.7°W) incoherent scatter radar and proposed an enhancement of the F-region electron temperature by 800 K resulting from neutral composition changes.…”
mentioning
confidence: 99%